Sterilization of rotary NiTi instruments within endodontic sponges. (4th September 2015) - Chan, H. W. A.; Tan, K. H.; Dashper, S. G.; Reynolds, E. C.; Parashos, P.
Abstract: Aim: To determine whether the following can be sterilized by autoclaving – endodontic sponges, rotary nickel–titanium (NiTi) instruments within endodontic sponges, and rotary NiTi instruments with rubber stoppers. Methodology: Sixty‐four samples of eight different endodontic sponges ( n = 512) were placed into brain heart infusion broth (BHI) for 72 h. An aliquot of this was then spread onto horse blood agar and cultured aerobically and anaerobically to test sterility at purchase. Bacterial suspensions of Enterococcus faecalis, Porphyromonas gingivalis and Geobacillus stearothermophilus in BHI were used to contaminate sterile sponges and rotary NiTi instruments (with and without rubber stoppers) inserted into sponges. The various samples were autoclaved and then cultured aerobically and anaerobically. Success of sterilization was measured qualitatively as no growth. The experiment was repeated with clinically used rotary NiTi instruments ( n = 512). All experiments were conducted in quadruplicate. Results: No sponges on purchase had microbial growth when anaerobically cultured but some did when aerobically cultured. All autoclaved sponges and instruments (within or without sponges, and with or without rubber stoppers) were associated with no microbial growth. All nonautoclaved positive control samples showed microbial growth. Conclusions: Autoclaving was effective in the sterilization of sponges and endodontic instruments. Endodontic sponges should be autoclaved before clinical use. For clinical efficiency and cost‐effectiveness, rotary NiTi instruments can be sterilized in endodontic sponges without removal of rubber stoppers.